Concept of photonic hook scalpel generated by shaped fiber tip with asymmetric radiation; Journal of Biophotonics; Vol. 14, iss. 2 - Minin I. V. Igor Vladilenovich; Minin O. V. Oleg Vladilenovich; Liu Yanyu; Tuchin V. V. Valery Viktorovich; Liu Cheng-Yang (2021, 2021)
Title screen